Getting stuck: A study of Indonesian EFL learners self-efficacy, emotional intelligence, and speaking achievement - Dian Rahma Santoso; Ghozali Rusyid Affandi; Yazid Basthomi (Studies in English Language and Education, 2024)
The problems of speaking mastery faced by EFL students in higher education are various. The frequency of making mistakes in completing specific tasks is because of poor communication skills. Students have minimum chances resulting lack of practice that affects their successful performance. Self-efficacy and emotional intelligence were determined to be two essential components to developing and improving learners speaking abilities. This study is purposed to investigate the correlation between self-efficacy, emotional intelligence, and the achievement of students English speaking. This study used a quantitative correlational design. The data are gathered by using a self-efficacy scale expanded from the General Self-Efficacy Skill (GSE), emotional intelligence was measured with the emotional intelligence scale adapted from the Emotional Regulation Questionnaire (ERQ), while the speaking achievement was administered to 100 students in public speaking class. The students performed a seven-minute speech and scored based on the content, proficiency, and delivery method. The data on self-efficacy and emotional intelligence were analyzed by using multiple correlations and multiple regressions. The finding shows a significant correlation between self-efficacy and students speaking achievement (F=9.510; p=0.0030.05), while the effect size of self-efficacy on students speaking achievement is 0.102 or 10,2 %. However, there is no correlation between emotional intelligence and speaking achievement (F=2.861; p=0.0940.05). Due to the absence of a significant relationship between emotional intelligence and speaking achievement then this makes the effect size of the emotional intelligence on speaking achievement very small which is 3.3%. Then, the best model to describe students achievement is by using self-efficacy variables and eliminating emotional intelligence variables (t=3.084; Sig. 0.0030.05). This study contributes to all speaking teachers being able to reveal the students self-efficacy and emotional intelligence toward learning speaking.